2004
DOI: 10.1016/j.jfms.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Pain management in cats—past, present and future. Part 2. Treatment of pain—clinical pharmacology

Abstract: Opioids have an unjustified reputation for causing mania in cats, but with refinements in dosing they are now used successfully in this species. The mu-opioid agonists are generally considered the best analgesics. Morphine (0.1-0.3 mg/kg) is effective in a clinical setting. Methadone (up to 0.5 mg/kg) has a similar profile to morphine. Pethidine (Demerol, meperidine; 2-5 mg/kg) is a useful analgesic with a faster onset but shorter duration of action than morphine. Oxymorphone and hydromorphone (0.05-0.1 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 84 publications
6
132
0
1
Order By: Relevance
“…The preoperative application of meloxicam reduces the systemic stress response, by decreasing the plasma cortisol and adrenaline (17,18). The peak of the analgesic effect of butorphanol is between the 30th and 60th min of intramuscular application (19), which corresponded to the lowest detected WBC, Ly, Gran in group ММ, in agreement with data from earlier research of ours regarding the blood hormonal levels in the same periods (9).…”
Section: S S U E 2 2 0 1supporting
confidence: 90%
“…The preoperative application of meloxicam reduces the systemic stress response, by decreasing the plasma cortisol and adrenaline (17,18). The peak of the analgesic effect of butorphanol is between the 30th and 60th min of intramuscular application (19), which corresponded to the lowest detected WBC, Ly, Gran in group ММ, in agreement with data from earlier research of ours regarding the blood hormonal levels in the same periods (9).…”
Section: S S U E 2 2 0 1supporting
confidence: 90%
“…23,34 The volumes for RBA and PBA in the present study were based on results for a study 26 in cat cadavers, where 1 and 4 mL resulted in appropriate intraconal distribution. However, although results of that study 26 indicated 4 mL was appropriate for PBA, a volume of 3 mL was used in the present study because of 2 concerns: ensuring we did not exceed a bupivacaine dose of 2 mg/kg to avoid systemic toxicosis, [35][36][37][38][39][40][41] and maintaining a bupivacaine concentration > 0.25% because lower concentrations of the anesthetic may lead to decreased efficacy. 4,42,43 Given that distribution of the injectate around the optic nerve was only 90° to 180° in 3 of 6 PBA-treated eyes, it is possible that a larger volume (4 mL) was indicated for PBA.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Nonsteroidal anti-inflammatory drugs also have been beneficial in the treatment of transitional-cell carcinoma in dogs. 53 These substances not only decrease the inflammatory reaction in the tumor tissue but also inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%